Impact of Monetary Policy on Economic Development in Nigeria - Ayorinde, Babatunde Femi (Journal of Business Management and Economic Development, 2025)
This research analysed how monetary policy affects Nigerian economic growth from 1986 until 2023. The study's dependent variable was Gross Fixed Capital Formation (GFCF), which represented economic growth, and its factors were money supply, exchange rate, private sector credit, inflation rate, and GDP. The study examined how money supply, exchange rate, private sector lending, and inflation effect Nigeria's economic development.    The auto regressive distributed lag (ARDL) model estimated that MS, EXCR, CPS, INFR, and GDP did not affect economic development over time. However, monetary policy indicators do not substantially impact Nigerian economic growth. To attract foreign investors, policymakers should keep the exchange rate favourable; the Nigerian government should use its monetary authority to boost the economy now and in the future; and to control inflation and boost economic growth, policymakers should regulate the money supply and exchange rate.